Optimizing prehospital care: a comprehensive review of evidence-based protocols for tension pneumothorax management - Alsamhari, Abdullah; Gilkaramenthi, Rafiulla; Alamer, Bader Hussain; Jebreel, Albaraa; Abdulbari, Hamdi Hasan; Mushawwah, Saad M.; Altaezi, Lara (Faculty of Medicine, Universitas Trisakti, 2025)
It is of the utmost importance to diagnose and treat tension pneumothorax (TPX) as soon as possible, because if not recognized and treated, it may swiftly cause collapse of the respiratory and circulatory systems. An estimated 5% of people with serious thoracic injuries may die from this avoidable cause, making it a leading cause of death in trauma and prehospital situations. Methods for diagnosis, procedures for intervention, and strategies for training are the primary foci of this study, which aims to provide a synthesis of evidence-based protocols for the prehospital treatment of TPX. A literature search was done on Pubmed and Google Scholars databases to identify the relevant literature from 2015 to 2025. This review focuses on the use of point-of-care ultrasonography to improve diagnosis accuracy and assesses the effectiveness of needle decompression and finger thoracostomy as first-line therapies. We will go over the main research that back these methods, how they differ between regions, and the difficulties of implementing them in prehospital care. Standardized training methods and further studies on appropriate intervention strategies are two of the significant gaps in the literature that are pointed out in this review. These results provide suggestions for improving prehospital care, increasing survival rates, and enhancing clinical practice. This review highlights current evidence-based strategies for diagnosing and managing tension pneumothorax (TPX) in prehospital settings. It emphasizes advancements such as point-of-care ultrasound (POCUS) and interventions such as needle decompression and finger thoracostomy. The review also addresses challenges in protocol implementation, especially in developing EMS systems such as in Saudi Arabia, citing issues such as training disparities, limited resources, and system readiness.